Highly sulfated hexasaccharide sequences isolated from chondroitin sulfate of shark fin cartilage: Insights into the sugar sequences with bioactivities - Shuji Mizumoto (2018)
Chondroitin sulfate (CS) chains regulate the development of the central nervous system in vertebrates and are linear polysaccharides consisting of variously sulfated repeating disaccharides, [-4GlcUAβ1-3GalNAcβ1-] n , where GlcUA and GalNAc represent d-glucuronic acid and N-acetyl-d-galactosamine, respectively. CS chains containing D-disaccharide units [GlcUA(2-O-sulfate)-GalNAc(6-O-sulfate)] are involved in the development of cerebellar Purkinje cells and neurite outgrowth-promoting activity through interaction with a neurotrophic factor, pleiotrophin, resulting in the regulation of signaling. In this study, to obtain further structural information on the CS chains containing d-disaccharide units involved in brain development, oligosaccharides containing D-units were isolated from a shark fin cartilage. Seven novel hexasaccharide sequences, ΔO-D-D, ΔA-D-D, ΔC-D-D, ΔE-A-D, ΔD-D-C, ΔE-D-D and ΔA-B-D, in addition to three previously reported sequences, ΔC-A-D, ΔC-D-C and ΔA-D-A, were isolated from a CS preparation of shark fin cartilage after exhaustive digestion with chondroitinase AC-I, which cannot act on the galactosaminidic linkages bound to D-units. The symbol Δ stands for a 4,5-unsaturated bond of uronic acids, whereas A, B, C, D, E and O represent [GlcUA-GalNAc(4-O- sulfate)] , [GlcUA(2-O-sulfate)-GalNAc(4-O-sulfate)], [GlcUA-GalNAc(6-O-sulfate)] , [GlcUA(2-O-sulfate)-GalNAc(6-O-sulfate)], [GlcUA-GalNAc(4-O-, 6-O-sulfate)] and [GlcUA-GalNAc], respectively. In binding studies using an anti-CS monoclonal antibody, MO-225, the epitopes of which are involved in cerebellar development in mammals, novel epitope structures, ΔA-D-A, ΔA-D-D and ΔA-B-D, were revealed. Hexasaccharides containing two consecutive D-units or a B-unit will be useful for the structural and functional analyses of CS chains particularly in the neuroglycobiological fields. © 2012 The Author.